2021
DOI: 10.3390/ijms22073560
|View full text |Cite
|
Sign up to set email alerts
|

MYB Transcription Factors and Its Regulation in Secondary Cell Wall Formation and Lignin Biosynthesis during Xylem Development

Abstract: The secondary wall is the main part of wood and is composed of cellulose, xylan, lignin, and small amounts of structural proteins and enzymes. Lignin molecules can interact directly or indirectly with cellulose, xylan and other polysaccharide molecules in the cell wall, increasing the mechanical strength and hydrophobicity of plant cells and tissues and facilitating the long-distance transportation of water in plants. MYBs (v-myb avian myeloblastosis viral oncogene homolog) belong to one of the largest superfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 163 publications
1
82
0
1
Order By: Relevance
“…The large size of MYB family reflects their importance and functional diversity in regulating plant physiological and biochemical processes. Previous studies depicted that MYBs are involved in plant development, cell shape and petal morphogenesis, cellular proliferation and differentiation, trichome development, phenylpropanoid metabolism, hormone responses, biotic and abiotic stress responses, etc ( Baillo et al, 2019 ; Cao et al, 2020 ; Wang et al, 2021 ; Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The large size of MYB family reflects their importance and functional diversity in regulating plant physiological and biochemical processes. Previous studies depicted that MYBs are involved in plant development, cell shape and petal morphogenesis, cellular proliferation and differentiation, trichome development, phenylpropanoid metabolism, hormone responses, biotic and abiotic stress responses, etc ( Baillo et al, 2019 ; Cao et al, 2020 ; Wang et al, 2021 ; Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drought, high salt, extreme temperatures, and other stresses all impact the yield and quality of C. wenyujin . The v-myb avian myeloblastosis viral oncogene homolog (MYB) superfamily is one of most significant transcription factor (TF) families in plants, which regulates plant growth, development, and a variety of physiological/biochemical processes ( Cao et al, 2020 ; Wang et al, 2021 ; Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary wall formation-related genes mainly comprise a series of NAM, ATAF1/2, and CUC2 (NAC) and v-myb avian myeloblastosis viral oncogene homolog (MYB) transcription factors (TFs) forming a hierarchical network that gradually regulates the synthesis of cellulose, hemicellulose, and lignin during secondary wall formation ( Nakano et al, 2015 ). Previous studies indicate that the biosynthesis of the xylem cell wall of Arabidopsis is mediated by a three-layer transcriptional regulation model ( Ko et al, 2014 ; Xiao et al, 2021 ). Recent studies have found a similar regulatory network in bananas, in which NAC and MYB TFs forming a complex transcriptional network that regulates secondary wall deposition ( Negi et al, 2017 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary wall formation-related genes mainly comprise a series of NAM, ATAF1/2, and CUC2 (NAC) and v-myb avian myeloblastosis viral oncogene homolog (MYB) transcription factors (TFs) forming a hierarchical network that gradually regulates the synthesis of cellulose, hemicellulose, and lignin during secondary wall formation (Nakano et al, 2015). Previous studies indicate that the biosynthesis of the xylem cell wall of Arabidopsis is mediated by a three-layer transcriptional regulation model (Ko et al, 2014;Xiao et al, 2021). Recent studies have found a similar regulatory network in bananas, in which NAC and MYB TFs forming a complex transcriptional network that regulates secondary wall deposition (Negi et al, 2017(Negi et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%